Theory on the Market: Panic, Incorporating. (31st July 2014) - Orr, Jackie
Abstract : This essay offers a feminist inquiry into the social and political economy of panic disorder. My guiding question: how to rework the dominant construction of panic disorder as a medical problem towards a critical understanding of panic as a social problem within the postmodern? I investigate panic as a material effect of new, disembodying technologies of commodity and gender production emerging out of increasingly liquid flows of transnational corporate capital. Refracted through a partial reading of Karl Marx, Ronald Reagan, Luce Irigaray, and Upjohn Co. corporate annual reports, this collage text attempts to perform the complex relationship between an individual woman's experience of panic and the social structuring practices that constitute and effect that experience. Such a project invites the difficult articulation of analysis and emotion, of theory and the body, which informs much of the work of contemporary feminist social critique.